Disclosure of Human Immunodeficiency Virus Serostatus to the Patient; Issues for Laboratory Staff - Maryam Riaz Tarar; Tahir Naeem; Muhammad Ebrahim Naeem (Shalamar Medical & Dental College, Lahore, Pakistan, 2019)
Background: The disclosure of positive HIV status to a patient is not an easy task. In the developed world with established protocols for doing this, it becomes relatively simpler to present the results to the patient. In underdeveloped countries like Pakistan, it is not easy for the laboratory personnel in particular to convey such results to the patient.  Case Presentation: The problem has been discussed in the light of two cases presenting to Shalamar Teaching Hospital. The first case is an example of "Provider referral" and the second one the "Self-referral". At the end, recommendations are made to effectively handle the situation in an underdeveloped setup like Pakistan. Discussion: Complete knowledge of the disease is an essential requirement for anybody from the pathology department contemplating this responsibility. In addition, all communications should be in the local language and the counselor must be able to address all the questions/concerns raised by the patients and/or their families. The counselor learns the skill more through supervised training rather than a taught course.  Conclusion: This responsibility should be accepted only if the laboratory staff has no other option.